The influence of job satisfaction, organizational commitment and pay satisfaction on turnover intention of academic staffs in selected private higher education institution in Kota Kinabalu, Sabah - Agnes Dansun (2014)
Various literature reviews have investigated employee turnover intention within both the private and public sectors. However, little is known about employee turnover intention within Private Higher Education Institution in Kota Kinabalu, Sabah. The purpose of this study is to explore the relationship between job satisfaction, organizational commitment and pay satisfaction on turnover intention among academic staffs in Private Higher Education Institution in Kota Kinabalu, Sabah. In this study, job satisfaction, organizational commitment and pay satisfaction acts as independent variables. Meanwhile, turnover intention acts as dependent variable. This study adopts correlational study survey to answer the three research questions developed. The method of data analysis includes descriptive statistics, confirmatory factor analysis and structural equation modeling (SEM). The results imply that relationship between job satisfaction and organizational commitment does not have significant effect on turnover intention. However, the result of the relationship between pay satisfaction shows a significant influence on turnover intention. The findings indicated that pay satisfaction is the root cause of turnover intention, while job satisfaction and organizational commitment has minor influence on the turnover intention. Limitations of the study and recommendations for future research are also presented in this study. This research should serve as a guide to management in Private Higher Education Institution, especially in Kota Kinabalu, Sabah to deepen their understanding of the employees' behavior and take the necessary steps to reduce the turnover intention.